O Sr. Enbutsu e a Imagem Fotográfica Reflexão em torno de duas obras de ]oão Penalva - Gaspar, Mariana Marin (Revelar: Revista de Estudos da Fotografia e Imagem, 2016)
First the images, then the words, later what's said about them, and finally what they suggest us and what we built from there. The proposal is to "question" two "text-images" that integrate the work of João Penalva, a contemporary Portuguese artist I admire for his claiming capacity, namely through the extensive narratives he constructs on documents, texts, photos, videos, objects and performing arts which interplay with each other, either by links, not always obvious, either by clear ambiguities to be undone by the pleasure and the eye's fabrication. The linkage of visuality and language, movement and sound, the usage and mastery of several media and various mediums, the crossing of the creative act with a curatorship activity fictional or merely suggested and the deconstruction of the conventional exhibition space, are some of the many artistic gestures that know matter to be known or devised, practices that may well represent axiomatic paradigms of contemporary art. 'Sumiko' and 'As if she could see him' are two ''portraits" of women with apparent analogies but whose concordance first derives from the following narrative and from the creation of the enigmatic character of the ''photographer" -Mr. Enbutsu -which in both cases acquires a central and impacting role. To a brief introduction that is to be understood as a consideration on the theme's relevance and of the somewhat experimental nature in the construction of a speech, follows an approach to the object, the two images in dialogue and confrontation, where the use of the phrase "multiple dialectics" stems not from the complex nature of the photography, but from the dialogical game triggered by the study and the questioning of the photographic as well as the reflective attitude it demands; potential ways will be sought to reflect upon the photographic image, controversial and noted ways, long-established: reality and fiction, word/text and image, creation and reception, among others